2016
DOI: 10.1016/j.scriptamat.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Peierls stress in face-centered-cubic metals predicted from an improved semi-discrete variation Peierls-Nabarro model

Abstract: In order to quantitatively predict Peierls stress, a semi-discrete variational Peierls-Nabarro model is improved by incorporating an additional gradient energy term into the energy functional. This gradient energy term is designed to effectively represent the influence of both the discreteness of atoms and the quick variations of the displacement profile in the dislocation core. Using face-centered-cubic metals as a model system for validation, we obtain a more accurate prediction of the displacement profile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Here, for simplicity, a uniform h ab g0 is used for all sets of αβfor each dislocation type. Regarding characterization, in GPN modeling of puretype dislocations in Ag, Al, and Cu, h ab g0 were determined by fitting the GPN-based disregistry profiles to MS-based ones [58]. Applying the same approach here would ideally entail characterizing h ab g0 by fitting the PFDD-based disregistry profile to that from DFT.…”
Section: Determination Of the Gradient Energy Coefficients η αβ G0mentioning
confidence: 99%
“…Here, for simplicity, a uniform h ab g0 is used for all sets of αβfor each dislocation type. Regarding characterization, in GPN modeling of puretype dislocations in Ag, Al, and Cu, h ab g0 were determined by fitting the GPN-based disregistry profiles to MS-based ones [58]. Applying the same approach here would ideally entail characterizing h ab g0 by fitting the PFDD-based disregistry profile to that from DFT.…”
Section: Determination Of the Gradient Energy Coefficients η αβ G0mentioning
confidence: 99%
“…These improved PN models have been examined and extended for predicting core structure and Peierls stress of dislocations in various crystals (Schoeck, 2012(Schoeck, , 2013Wang et al, 2014a), and even for Escaig stress assisted dislocation cross-slip in FCC metals (Lu et al, 2004). Particularly, the recently developed semi-discrete variational Peierls-Nabarro (SVPN) model (Liu et al, 2016) have been demonstrated to obtain a more accurate prediction of core structure and Peierls stress of dislocations in FCC metals, as well as the right trend in the variation of the stacking fault width as the dislocation overcomes the Peierls barrier. In addition, the improved SVPN model can also predict the dislocation profile much more efficiently than atomistic simulations by numerically minimizing the dislocation energy functional.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we apply the improved SVPN model (Liu et al, 2016) to investigate the effects of the Escaig stress on core structure and Peierls stress of dislocations in FCC metals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations